2010
DOI: 10.1016/j.neulet.2010.04.073
|View full text |Cite
|
Sign up to set email alerts
|

Passively viewing negatively valenced baby faces attenuates left amygdala activity in healthy females scoring high on ‘Harm Avoidance’

Abstract: The amygdalae play an important role in the evaluation and processing of emotionally salient visual stimuli. However, individual differences in personality traits, such as Harm Avoidance (HA), have been reported to influence emotional amygdalae responses. To trigger strong approach and withdrawal-related emotions in 'never depressed' young female subjects under fMRI, we presented them with blocks of happy 'healthy' baby faces and baby faces disfigured by severe dermatological conditions and we integrated the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
2
18
0
2
Order By: Relevance
“…This study revealed an increased left lateralized amygdala response to the negative stimuli in the high HA participants while no lateralization of the amygdalae response was observed in the low and average HA participants. Contrary to this, the [29] study revealed a negative correlation between the left amygdala activation and HA during the sustained processing of negative stimuli, probably due to an increased tendency in the high HA participants to shift attention away from the negative stimuli in an attempt to control the induced emotional reaction.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…This study revealed an increased left lateralized amygdala response to the negative stimuli in the high HA participants while no lateralization of the amygdalae response was observed in the low and average HA participants. Contrary to this, the [29] study revealed a negative correlation between the left amygdala activation and HA during the sustained processing of negative stimuli, probably due to an increased tendency in the high HA participants to shift attention away from the negative stimuli in an attempt to control the induced emotional reaction.…”
Section: Introductionmentioning
confidence: 66%
“…These pictures were similar to the stimuli used in our previous studies [29,30]. The pictures for the positive stimuli were collected from family photos from staff members and from the Internet, while those for the negative stimuli originated from the dermatological literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous fMRI research has reported a reduction in amygdala activity associated with aversive photos of baby faces (i.e., baby faces disfigured by dermatological conditions) in individuals high in harm avoidance, a personality construct characterized as a general inclination to respond intensely to aversive stimuli, including shyness behavior (Baeken et al, 2010). Although it is difficult to compare across ERP and fMRI methodologies, the high temporal resolution of ERPs and our current findings may indicate that such reductions in amygdala activity to aversive or stressful stimuli as a function of personality may begin as early as 80 ms post-stimulus onset in extrastriate visual cortex along the ventral visual pathways that generate P1 activity (Hillyard & Anllo-Vento, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study reported that harm avoidance, a personality construct characterized as a general inclination to respond intensely to aversive stimuli, was related to a reduction of amygdala activity in response to aversive photos of baby faces (i.e., baby faces disfigured by dermatological conditions) but not to photos of happy baby faces (Baeken et al, 2010). Other research found trait disgust (i.e., disgust sensitivity) to be related to reductions of amygdala activity during imagined visualizations of previously presented photos that were shown to induce disgust (Schienle, Schäfer, & Vaitl, 2008), whereas such reductions were not reported for happy photos.…”
Section: Vigilance-avoidance Hypothesismentioning
confidence: 99%